2018
DOI: 10.1111/trf.14783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a large data set to identify predictors of blood transfusion in primary total hip and knee arthroplasty

Abstract: The risk factors identified in the current study can provide specific, personalized perioperative ALBT risk assessment for a patient considering lower limb TJA. Furthermore, the predictive accuracy of the RF algorithm was significantly higher than that of LR, making it a potential tool for future personalized preoperative prediction of risk for perioperative ALBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 49 publications
4
47
1
2
Order By: Relevance
“…The mean age of this cohort was 54.8 years, in contrast to previously reported 64.7–71.0 years in western countries. However, data of 7477 patients from 26 university teaching hospitals in China suggested that the mean age of Chinese THA patients was 57.6 ± 18.2 years. Besides, Chan et al .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The mean age of this cohort was 54.8 years, in contrast to previously reported 64.7–71.0 years in western countries. However, data of 7477 patients from 26 university teaching hospitals in China suggested that the mean age of Chinese THA patients was 57.6 ± 18.2 years. Besides, Chan et al .…”
Section: Discussioncontrasting
confidence: 84%
“…High prevalence of osteonecrosis of femoral head (ONFH) and developmental dysplasia of the hip (DDH) in contrast to very low prevalence of primary hip osteoarthritis have been observed in the Chinese population. Besides, due to different races, the Chinese THA patients have much lower age and BMI than those reported abroad. As a result, we considered that the predictors for LOS in western literatures may be nonequivalent for those of Chinese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Using modern machine learning tools, we could reliably predict which patients will be in need for transfusion of RBCs with a manageable number of features provided at hospital admission. In contrast to other studies, we did not restrict prediction to one patient group, like others have done 18,19 but provided a model that can be used over a broad range of indications. However, although this prediction has proven to be very reliable for classification of "transfusion" vs "no transfusion," we found out for our database that the total number of RBC transfusions per patient and the occurrence of massive transfusion in a specific patient cannot be predicted reliably, a phenomenon that has been described in liver transplantations by other groups.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [13] based on a nationwide inpatient sample database reported that TKA and THA were among the top 10 most-frequent procedures requiring transfusion in the USA. Furthermore, blood transfusion was related to numerous serious complications such as viral infection, anaphylactic and hemolytic reactions, longer PLOS, deep vein thromboembolism, high hospitalization costs, and increased in-hospital mortality [1416]. Allogeneic blood reserves are often insufficient worldwide; consequently, reducing the transfusion rate is essential for patients undergoing TKA or THA.…”
Section: Discussionmentioning
confidence: 99%